A novel electrochemically active and Fe(III)-reducing bacterium phylogenetically related to Aeromonas hydrophila, isolated from a microbial fuel cell - Pham, CA; Jung, SJ; Phung, NT; Lee, J; Chang, IS; Kim, BH; Yi, H; Chun, J (ELSEVIER SCIENCE BV, 2003)
A facultative anaerobic bacterium was isolated from a mediator-less microbial fuel cell fed with artificial wastewater containing acetate and designated as PA3. The isolate was identified as a strain of Aeromonas hydrophila based on its biochemical, physiological and morphological characteristics as well as 16S rDNA sequence analysis and DNA-DNA hybridization. PA3 used glucose, glycerol, pyruvate and hydrogen to reduce Fe(III), nitrate and sulfate. Cyclic voltammetry showed that PA3 was electrochemically active and was the culture collection strain A. hydrophila KCTC 2358. Electricity was generated from a fuel cell-type reactor, the anode compartment of which was inoculated with cell suspensions of the isolate or A. hydrophila KCTC 2358. The electrochemical activities are novel characteristics of A. hydrophila. (C) 2003 Federation of European Microbiological Societies. Published by Elsevier Science B.V. All rights reserved.
Keywords: SHEWANELLA-PUTREFACIENS; ELECTRON-ACCEPTORS; REDUCING BACTERIUM; REDUCTION; FE(III); FERMENTATION; CAPSULATUS; SEDIMENT; MN(IV); NOV